Herbal Treatment, Usage Frequency, Types and Preferences in Tikrit city, Iraq - Abdulkhalk Yehea Al-Handh, Ban (Tikrit Journal of Pharmaceutical Sciences, 2023)
Alternative treatment usage is increasing around the world although treatment methods are becoming more modern and more drugs are made available. A cross sectional study was conducted to determine the incidence of treatment with herbs as an alternative treatment method in Tikrit city and the reasons for its usage. in a sample (number =1268) in the age group (20 – 50) years. duration of the study extended from the January 1, 2011 to December 31, 2011. In Tikrit there were 15 herbal stores ,and 35 pharmacies deal with herbal treatment such as nettle, St. John’s wort, rosemary, garden sage and hawthorn, oleander and thyme. The study was carried out with a questionnaire to persons who had received preliminary information. After the subjects were informed of the study, the analysis of medicinal plants by the participants. Nine hundred sexist two(75.9%) of those participating in the study reported that they had used a herbal medication at least once. The main health problems leading to the usage of herbal medication for their treatment was hair loss - hair care, hemorrhoids, skin care, peptic ulcer - gastritis and infertility. The main reason for interest in herbal treatments was “hoping to find a herbal medicine which could help treat their condition”. People living in Tikrit city has a high rate of alternative medicine usage and regular studies are required to show changes over time.